The use and effectiveness of high-fidelity simulation in health professions education: current update. (December 2022) - Abdulhussain, Yasmin; Ghelani, Hardik; Henderson, Helen; Sudhir, Meghana; Mascarenhas, Sharon; Radhakrishnan, Rajan; Jan, Reem Kais
Over the past 10 years, there has been an increase in the use of high-fidelity simulation (HFS) as a tool to support and enhance learning in health profession programs. In this article, we review the utilization of HFS in biomedical (basic science) courses for health professions students, and we compare its effectiveness to traditional teaching methods. Studies exploring the impact of HFS on students and residents were included in the review. The use of HFS is more prevalent in advanced clinical settings such as in training residents and nurses than in teaching students in preclinical years. When compared to traditional teaching methods, HFS is noted to be superior in delivering core biomedical concepts to students and healthcare professionals. However, a few studies showed no significant differences between HFS and traditional teaching methods when assessing clinical management skills. Overall, HFS is a valuable teaching tool which enhances knowledge retention and clinical skill acquisition in medical education.